Halogen element modified titanium dioxide for visible light photocatalysis - Sun, Hongqi; Wang, Shaobin; Ang, Ming; Tade, Moses; Li, Qin (Elsevier BV, 2010)
Halogen elements, i.e. fluorine, chlorine, bromine, and iodine, have attracted intensive interests in modification of TiO2 for photocatalytic oxidation of organic pollutants under visible light irradiation. Compared to other metal and non-metal elements, halogens show 3-fold advantages, such as improvement of UV activity, various cations or anions for substitution of Ti4+ and/or O2− in the TiO2 matrix, narrowing the band gap of TiO2 and tuning the band position. In this paper synthesis, physicochemical properties, mechanism of visible response, and photocatalytic activities of halogen modified TiO2 are reviewed. It is found that introduction of a halogen element into TiO2 crystals could lead to the enhancement of surface acidity, formation of surface hydroxyl radicals, more active sites, creation of oxygen vacancies or Ti3+, narrowing the band gap and tuning the valence band position. As a consequence, halogen modified TiO2 exhibited high activity for organics oxidation under visible light radiation in aqueous and gas phases.